(untitled) (Psychology Travelogs, 2025)
The article presents a summary of the results of research into the links between loneliness and student academic performance. Loneliness is considered to be a mental state that develops as a result of insufficient social support and limited interpersonal contacts. For students, such manifestations are accompanied by emotional tension, decreased cognitive activity, and uneven academic engagement. In the modern educational environment, which combines intense workloads, autonomous learning, and changes in social interaction formats, this condition is becoming increasingly common. The aim of the study was to identify the relationships between the level of loneliness, emotional manifestations, cognitive activity, and academic motivation of students. The empirical part is based on the results of a survey of 30 people using standardised methods: DASS-21, UCLA Loneliness Scale, Montreal Cognitive Assessment, and Academic Motivation Scale. The collected data made it possible to form an integrated picture of the psychological state of the participants and to determine the interdependencies between the variables under study. The results indicate the prevalence of emotional tension among students and increased anxiety in cases of increased loneliness. A decrease in concentration and information processing speed was observed in students with high loneliness scores, accompanied by instability in academic motivation and a shift in focus from internal to external motives. Correlation analysis confirmed stable links between loneliness and emotional manifestations, as well as between loneliness and a decrease in academic interest. These results indicate that loneliness can affect academic performance through emotional vulnerability and uneven cognitive engagement.